THE EFFECT OF TEACHING-LEARNING ASSIGNMENT METHOD IN CIVIC LECTURE FOR ELEMENTARY ON STUDENTS PEDAGOGIC COMPETENCY - ., Santa; Mirawati, Mira (UNIVERSITAS PAKUAN, 2020)
Title of the research is the effect of teaching-learning assignment of civic lecture for elementary school on students pedagogic competency. This research is aimed at finding out the effect of teaching-learning assignment method of civic lecture for elementary school on students pedagogic competency. The research was conducted on students of PGSD Semester 4th academic year 2018-2019 with total sample of 130. Survey method with causality approach is used in this research. Data analysis technique used in this research is correlation statistic test, simple linear regression. Hypothesis testing is done under significance standard of 0,05. The result of the research concluded that teaching-learning assignment on civic teaching for elementary school gives effect on pedagogic competency. It can be seen through correlation coefficient (rxy) between assignment (X) and pedagogic competency (Y) which resulted in score of r = 0,656. Casual coefficient is consulted through interpretation table of pearson product moment correlation (r) which is at strong effect. Regression equation for significance regression test is Fcount = 0,9842 with Ftabel(0,05) = 1,60 and Ftabel(0,01) = 1,93 with dkpembilang = 27 and dkdeterminer = 101. So that Fcount Ftabel(0,05) Ftabel(0,01) = 0,9842 1,60 1,93 therefore it can be concluded that Fcount Ftabel it means linear hypothesis is accepted, it that case data from pedagogic competency (Y) and assignment (X) have linear sphere relationship. The result of the research shows that pedagogic competency can be affected by teaching-learning assignment method during teaching-learning process of civic material in elementary school.